UJI AKTIVITAS ANTIOKSIDAN PADA KULIT JERUK MANIS (CITRUS SINENSIS)SEBAGAI ALTERNATIF BAHAN PEMBUATAN MASKER WAJAH - Eza Ria Friatna, Achmad Rizqi, dan Tanti Hidayah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
This study was conducted to test the antioxidant content from orange peel powder which was thenused as the material of face mask.The testing method of the antioxidant activity of the orange peel extract used in this study was themethod of DPPH by considering 0.66 gram of the sample which was then added with 10 ml of methanoland messed by using a centrifuge for three minutes. The next step was taking 1.5 ml of filtrate andputting it into a test tube and adding it with 1 ml of DPPH solution. Two samples of solution were made,sample A and sample B. Next, negative control solution was made by mixing 1 ml of sample and 9 ml ofmethanol. The next step was leaving the four kinds of solution in a dark room for 20 minutes. After that,the absorbance (optical density) of the four kinds of solution was measured by using spectrophotometerwith the maximum wave length of 518 nm.Based on the measurement of the data gained, it was revealed that the value of the antioxidantactivity ranged from 66.84% to 68.91%. It indicated that the ornage peel could be used as the materialfor producing face mask.Key words: orange peel, antioxidant, face mask